Journal of Human Sport and Exercise - 2020 - Spring Conferences of Sports Science 2020
DOI: 10.14198/jhse.2020.15.proc3.03
|View full text |Cite
|
Sign up to set email alerts
|

A study on psychological training of eSports using digital games: Focusing on rhythm game

Abstract: Incidentally, several studies have mentioned that digital games or video games have a positive impact on psychological skills (Green, et al., 2003; Pessoa, 2009; Anguera, et al., 2013). Thus, this study aimed to examine the psychological skills focusing on selective attention by comparing the power change in the beta wave band of the EEG during game play and the results of the trail making test (TMT) conducted before and after. Participants were ten male college students who usually play game for at least one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The human psychological (mental) state can also be reflected by recording electrical signals obtained from electrodes placed on the scalp. For example, Hagiwara, Akiyama, et al (2020) measured the EEG of FP1 (10-20 system) located in the left frontal lobe of participants performing the rhythm game and noted an increase in selective attention levels. In addition, Hagiwara et al (2019) found that the concentration values during gameplay were significantly higher compared to the baseline, when the soccer game was performed for 10 minutes.…”
Section: Methods For Measuring and Assessing Psychological Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…The human psychological (mental) state can also be reflected by recording electrical signals obtained from electrodes placed on the scalp. For example, Hagiwara, Akiyama, et al (2020) measured the EEG of FP1 (10-20 system) located in the left frontal lobe of participants performing the rhythm game and noted an increase in selective attention levels. In addition, Hagiwara et al (2019) found that the concentration values during gameplay were significantly higher compared to the baseline, when the soccer game was performed for 10 minutes.…”
Section: Methods For Measuring and Assessing Psychological Statesmentioning
confidence: 99%
“…Therefore, in the present study, we used the same EEG measures as in the studies by Hagiwara et al (2019); Hagiwara, Akiyama, et al (2020). Specifically, the participants wore an EEG device on their heads, and electrodes were attached to their ears and forehead to obtain data on the intensity of alpha (8-13 Hz) and beta (13-40 Hz) waves, at 1-second intervals.…”
Section: Methods For Measuring and Assessing Psychological Statesmentioning
confidence: 99%